Mengukur Kesehatan Keuangan BUMN Terdaftar Di BEI Pada Saat Pandemi Covid-19 - Lim, Setiadi Alim (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2024)
This study aims to determine the financial health of BUMN (State-Owned Enterprises) listed on the Indonesia Stock Exchange (IDX) during the Covid-19 pandemic (period 2020-2022). To determine the financial health of the company, six multiple discriminant analysis (MDA) models were used, namely: the Altman model, the Fulmer model, the Grover model, the Springate model, the Taffler model, and the Zmijewski model. This study is classified as a descriptive exploratory study. Sampling used the non-probability purposive sampling method. There were ten companies taken as samples. The results of the study show that the use of several models can provide the same analysis results, but can also produce different analysis results. In general, if the financial health of a company is very healthy, then the use of any model will provide the same analysis results. Likewise, if the financial health of a company is not good, then the use of any model will give the same results. The results of the study show that there are five companies whose financial health is indicated to need attention, namely PT Adhi Karya (Persero) Tbk. (ADHI), PT Pembangunan Perumahan (Persero) Tbk. (PTPP), PT Wijaya Karya (Persero) Tbk. (WIKA), PT Waskita Karya (Persero) Tbk. (WSKT), and PT Jasa Marga (Persero) Tbk. (JSMR). In addition, the results of the study also showed that there were two companies whose financial health performance was indicated to be very good in all (six) models used, namely PT Bukit Asam Tbk. (PTBA) and PT Telekomunikasi Indonesia (Persero) Tbk. (TLKM). Keywords: financial health, bankruptcy, state-owned enterprises.